Team Games Tournament Learning Model for Low Class Primary School Students Balance Materials - Qolbi, M. Hafid; Julianti P., Eva; U.S., Oman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research explains the team games tournament learning model for balance material for lower elementary school students, using Research and Development research. This research created a product design of 15 learning models and then validated them with justification tests by learning experts. The validation tests used were expert justification test with 3 experts, namely experts in the field of learning. The average pretest result before treatment of the team games tournament learning model for balance material was 21.20 and after treatment the average was 28.10. In the future, this research aims to serve as reference material for teachers and students who will develop this model. Providing more models in learning to improve the results of the learning process, especially balance material for students.